An estimated DSGE model of the Hungarian economy - Zoltán M. Jakab; Balázs Világi (Magyar Nemzeti Bank, 2008)
This paper presents and estimates a dynamic stochastic general equilibrium (DSGE) small-open-economy model for the Hungarian economy. The model features different types of frictions, real and nominal rigidities which are necessary to replicate the empirical persistence of Hungarian data. Bayesian methods are applied, and the structural break due to changing monetary regime over the studied period is explicitly taken into account in the estimation procedure. A real-time adaptive learning mechanism describes agents' perception on underlying inflation. This creates an additional inertia in inflation. We describe the properties of the estimated model by impulse-response analysis, variance decomposition and the analysis of identified structural shocks. Our results are compared with that of estimated euro-area DSGE models, and estimated non-DSGE models of the Hungarian economy. As a robustness check, a model without real time adaptive learning is also estimated and it's results are also compared to those of the original model.
Keywords: E40; E50; 330; New Keynesian models; DSGE models; small open economy; Bayesian econometrics; Dynamisches Gleichgewicht; Kleine offene Volkswirtschaft; Bayes-Statistik; Schätzung; Ungarn